In-Situ hygrothermal evaluation of ventilation block as adaptive climate buffer in contemporary tropical house of Indonesia (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Within tropical urban environments, passive cooling strategies have become increasingly essential in mitigating the escalating energy consumption associated with achieving indoor thermal comfort. Among the passive cooling approaches suitable for the hot-humid tropical climate of Indonesia, comfort-oriented ventilation through the application of ventilation blocks demonstrates considerable potential. Nevertheless, the actual thermal behavior and environmental performance of ventilation blocks as an integrated system within tropical residential architecture remain insufficiently investigated. This study examines the hygrothermal performance of ventilation blocks as adaptive climatic buffers in urban housing environments. Four contemporary residential buildings in Surabaya were selected as case studies, representing the hot-humid climatic characteristics of Indonesia. Field measurements were conducted over a continuous 30-day monitoring period using temperature and humidity sensors. The instruments were positioned at a height of 1.5 m above the floor surface. Buffered hygrothermal conditions were successfully achieved within the indoor spaces of the contemporary houses. This environmental condition produced the lowest average indoor temperature (28.1°C), the longest thermal comfort duration (16 hours), and the smallest temperature and humidity fluctuations (2.7°C and 11%). Configurations incorporating high opening ratios and hygroscopic materials demonstrated greater effectiveness in moderating moisture levels. Meanwhile, configurations characterized by moderate opening ratios and material thicknesses generated the most optimal spatial heat propagation performance and the longest cooling duration.
Keywords: Contemporary tropical housing; Hygrothermal; In Situ field measurement; Thermal buffer; Ventilation block